IEEE 1451.2-based sensor system with JAVA-TEDS software tool - Rossi, Silvano R.; Rodrigues da Silva, Alexandre C.; Santos Filho, Tércio A. (ТНЕУ, 2009)
This work presents the implementation of a microcontroller-based Smart Transducer Interface Module based on the IEEE 1451.2 standard and a Java-TEDS software tool development to generate the electronic data for each transducer channel implemented in the smart module. The module, with two transducer channels was implemented with a PIC16F876A® microcontroller and programmed in C language. A software support resource has been developed in order to generate the data for the Transducer Electronic Data Sheet descriptive memory. This software resource is fully based on Java language. When generated, the TEDS data blocks can be stored in the program memory module of the microcontroller. Methodology and results are presented and discussed.
Keywords: Microcontroller; Transducer; Interface; IEEE1451; STIM; TEDS